Fact or Fiction-Accelerometry Versus Self-Report in Adherence to Pediatric Concussion Protocols: Prospective Longitudinal Cohort Study - Carol DeMatteo; Sarah Randall; Josephine Jakubowski; Kathy Stazyk; Joyce Obeid; Michael Noseworthy; Michael Mazurek; Brian W Timmons; John Connolly; Lucia Giglia; Geoffrey Hall; Chia-Yu Lin; et al. (JMIR Publications, 2024)
Abstract BackgroundConcussion, or mild traumatic brain injury, is a growing public health concern, affecting approximately 1.2% of the population annually. Among children aged 1‐17 years, concussion had the highest weighted prevalence compared to other injury types, highlighting the importance of addressing this issue among the youth population. ObjectiveThis study aimed to assess adherence to Return to Activity (RTA) protocols among youth with concussion and to determine if better adherence affected time to recovery and the rate of reinjury. MethodsChildren and youth (N=139) aged 5‐18 years with concussion were recruited. Self-reported symptoms and protocol stage of recovery were monitored every 48 hours until symptom resolution was achieved. Daily accelerometry was assessed with the ActiGraph. Data were collected to evaluate adherence to the RTA protocol based on physical activity cutoff points corresponding to RTA stages. Participants were evaluated using a battery of physical, cognitive, and behavioral measures at recruitment, upon symptom resolution, and 3 months post symptom resolution. ResultsFor RTA stage 1, a total of 13% of participants were adherent based on accelerometry, whereas 11% and 34% of participants were adherent for stage 2 and 3, respectively. The median time to symptom resolution was 13 days for participants who were subjectively reported adherent to the RTA protocol and 20 days for those who were subjectively reported as nonadherent (P ConclusionsOverall, adherence to staged protocols post concussion was minimal when assessed with accelerometers, but adherence was higher by self-report. More physical activity restrictions, as specified in the RTA protocol, resulted in lower adherence. Although objective adherence was low, reinjury rate was lower than expected, suggesting a protective effect of being monitored and increased youth awareness of protocols. The results of this study support the move to less restrictive protocols and earlier resumption of daily activities that have since been implemented in more recent protocols.